Antimicrobial and antibiofilm effects of cyclic dipeptide-rich fraction from Lactobacillus plantarum loaded on graphene oxide nanosheets - Dezaki, Farid Shirmardi; Narimani, Tahmineh; Ghanadian, Mustafa; Bidram, Elham; Poursina, Farkhondeh (Frontiers in Microbiology, 2024)
One effective method to combat bacterial infections is by using bacteria itself as a weapon.Lactobacillus is a type of fermenting bacterium that has probiotic properties and has demonstrated antimicrobial benefits against other bacteria. Cyclodipeptides (CDPs), present in the supernatant of Lactobacillus, possess several antimicrobial properties. In this study, the CDP fraction was isolated from the supernatant of Lactobacillus plantarum (L. plantarum). This fraction was then loaded onto graphene oxide nanosheets (GO NSs). The study assessed the substance's ability to inhibit bacterial growth by using the minimum inhibitory concentration (MIC) method on A. baumannii and S. aureus strains that were obtained from clinical samples. To determine the substance's impact on biofilm formation, the microtiter plate method was used. Moreover, the checkerboard technique was employed to explore the potential synergistic effects of these two substances. According to the study, the minimum inhibitory concentration (MIC) of the desired compound was found to be 1.25 mg/mL against S. aureus and 2.5 mg/mL against A. baumannii. Furthermore, at a concentration of 10 mg/mL, the compound prevented 81.6% (P<0.01) of biofilm production in A. baumannii, while at a concentration of 1.25 mg/mL, it prevented 47.5% (P<0.05) of biofilm production in S. aureus. The study also explored the synergistic properties of two compounds using the checkerboard method. In general, we found that GO NSs possess antimicrobial properties and enhance cyclodipeptides' activity against S. aureus and A. baumannii.